Impact of Human Body Dissection on First Year Undergraduate Medical Students - Shah, Sandip; Koirala, Sarun; Khanal, Laxman; Baral, Presha (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: The first contact with the dissection hall is an unforgettable, stressful but important step in the medical education. The present study aimed to assess the stress experienced just after one week of first dissection (IES1) and compare it with impact after 12 weeks (IES2) of first experience.Methods: In this prospective cohort study, we enrolled 100 first year medical students of B. P. Koirala Institute of Health Sciences attending the cadaveric dissection. The questionnaire for Impact Event Scale (IES) was administered on two separate occasions after the human body dissection. Along with overall score for impact event, we also assessed the sub-scores of Intrusion and Avoidance.Results: The percentage of students having clinically important reaction (a score of 20 or above) after one week of first cadaveric dissection in both sub-scales of Intrusion and Avoidance were 2% and 6% respectively but were found to be reduced to 1% each after 12 weeks. The overall scores indicating traumatic stress reaction was found to be reduced to 2% from 8%. The comparison between IES1 and IES2 using Wilcoxon signed ranked test showed statistically significant difference (p < 0.001). The bivariate correlation analysis between IES 1 and IES 2 showed positive correlation with statistically significant level (rs = 0.25; p < 0.001).Conclusion: Overall score in students having traumatic stress reaction dropped by 6% after 12 weeks. The stress related to the human body dissection with respect to both Intrusion and Avoidance sub-scales in medical students reduced after the period of 12 weeks of first cadaver dissection.